2022
DOI: 10.1101/2022.02.23.481342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fate-resolved gene regulatory signatures of individual B lymphocytes in the early stages of Epstein-Barr Virus infection

Abstract: Epstein-Barr Virus (EBV) infection of B lymphocytes elicits diverse host responses via complex, well-adapted transcriptional control dynamics. Consequently, this host-pathogen interaction provides a powerful system to explore fundamental cellular processes that contribute to consensus fate decisions including cell cycle arrest, apoptosis, proliferation, and differentiation. Here we capture these responses and fates with matched single-cell transcriptomics and chromatin accessibility, from which we construct a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 210 publications
0
3
0
Order By: Relevance
“…Here we perform an in-depth analysis of the scRNA data, develop a refined germinal center (GC) model of EBV early infection, and detail previously uncharacterized EBV-infected B cell niches. Integration of the scATAC-seq data as well as development, validation, and implementation of a bioinformatic workflow to predict state-resolved regulatory relationships are reported in a companion piece (SoRelle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Here we perform an in-depth analysis of the scRNA data, develop a refined germinal center (GC) model of EBV early infection, and detail previously uncharacterized EBV-infected B cell niches. Integration of the scATAC-seq data as well as development, validation, and implementation of a bioinformatic workflow to predict state-resolved regulatory relationships are reported in a companion piece (SoRelle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies have revealed the landscape of both tumor and infiltrating immune cells in NPCs that are associated with prognosis (234,235,408). Additionally, scRNA-seq are now used to delineate rare cell subpopulations such as cancer stem cells, cell-cell interactions via receptor-ligand analyses, cell differentiation via trajectory and time-resolution analyses (409). Additional steps also allow TCR, BCR and cell-surface protein expression (CITE-seq) sequencings at the single cell level to supplement scRNA-seq for the study of the diversity of immune cells.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…It is important to note that most of these assays utilize bulk sample processing and therefore observations in heterogeneous cell populations should be carefully interpreted, as discussed above for bulk RNA-seq. Recently, the limits of some of these technologies have been pushed to the single cell level and integrated into scRNA-seq platforms to enable multiomics based investigation of EBV infection (409).…”
Section: Other Sequencing Technologiesmentioning
confidence: 99%